8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)
4x2 + 12x + 5 = (2x + 1)(2x + 5).
-((4x + 1)(x - 1))
4x2 + 12x + 5 = 4x2 + 2x + 10x + 5 = 2x(2x+1) + 5(2x+1) = (2x+1)(2x+5)
(2x + 1)(2x + 1) or (2x + 1)2
8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)
4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x
4x2 + 12x + 5 = (2x + 1)(2x + 5).
x3 + 4x2 + x + 4 = (x + 4)(x2 + 1)
Given 3x3 + 4x2 +x + 7 is divided by x2 + 1, find the results:
The quadratic 4x2+24x+11 = (2x+1)(2x+11)
This is how I did it:8x3+4x2+6x+3[8x3+4x2]+[6x+3][(4x2)(2x+1)]+[(3)(2x+1)]....as you can see, this is in the general form of ab+cb, which factored is b(a+c), so:(2x+1)(4x2+3)
-((4x + 1)(x - 1))
2(x + 1)(2x + 1)
4(x + 1)(x + 1)
4x2 + 12x + 5 = 4x2 + 2x + 10x + 5 = 2x(2x+1) + 5(2x+1) = (2x+1)(2x+5)
(4x + 1)(x + 5)